Detailed Study on the Effect of NeuroGen® Nerve Support Supplement on Pillar Pain after Endoscopic Carpal Tunnel Release - Michael J. Fitzmaurice (Current Topics in Medicine and Medical Research Vol. 12, 2021)
Pillar pain is one of the most common complications after carpal tunnel surgery and has an occurrence from 7% - 61%. 61 patients with clinically diagnosed and electromyographically confirmed carpal tunnel syndrome were enrolled in a prospective study to evaluate the effectiveness of a nerve supplement on pillar pain after carpal tunnel surgery. All of the patients underwent endoscopic carpal tunnel release. 15 of the patients also took the nerve support supplement NeuroGen® as part of their perioperative treatment. The supplement group demonstrated a significantly lower amount of pillar pain (VAS) at initial follow up compared to the control group (1.13 and 4.05 respectively). 46% (7/15) of the supplement group were completely free of pillar pain compared to only 9% (4/46) of the control group at the first follow up. 53% (8/15) of the NeuroGen® group did not require any pain medications compared to 35% (16/46) of the control group. The Nerve supplement NeuroGen® significantly reduces pain after carpal tunnel surgery. This decrease in pain results in less post-operative medication required and an earlier return to activity. Further studies will evaluate the effectiveness of the supplement on nerve regeneration after surgical decompression.